Protocol for a randomized and a non-randomized controlled trial testing Daily Growth: a personalised ‘ecological momentary intervention’ parenting app for parents and carers of children aged 2–5 years - Elizabeth M. Westrupp; Maria Bates; Kelsie J. Bufton; Tomer B. Berkowitz; Melody Popple; Gabriella L. King; Sara Jones; Jem Stone; Joost J. C. Funke Kupper; John W. Toumbourou; Chandan Karmakar; Sophie S. Havighurst; et al. (BMC Psychology)
Abstract Background Children’s ability to regulate their emotions is a critical protective factor for early mental health and development and is strongly influenced by parenting. Parenting programs can improve these outcomes for children, however, most families, particularly those from diverse or disadvantaged backgrounds, never receive evidence-based support. There is a pressing need for parenting programs that are widely accessible and meaningfully tailored to individual needs and real-time parenting challenges to enhance parent engagement. This protocol outlines the design of two staged trials testing Daily Growth, a universal parenting app for parents/carers of children 2–5 years. The first trial will evaluate the app’s effectiveness as implemented in a real-world community-based trial, while the second will develop and test a machine learning system for personalising support based on Trial 1 data. Methods In Trial 1, parents/carers (n = 1,650) will be recruited and randomised to one of five groups: 150 to active control (government parenting website); 100 each to one of three programs (Emotion Coaching, Active Play, or Wayapa Wuurrk); 1,200 to a non-personalised random combination of all three. Trial 2 (non-randomised) will recruit 400 parents/carers to receive personalised support, with program content from the three programs allocated via a machine learning algorithm based on baseline data. Both trials will run for six weeks where participants will receive twice-daily prompts to complete a 1-min pre-ecological momentary intervention (pre-EMI) survey and non-control participants offered three-minute videos tailored to specific parenting challenges. A post-EMI survey will be delivered 15 min later to assess immediate outcomes. Participants in both trials will complete baseline, six-week, and six-month follow-up surveys. Outcomes from the non-personalised trial will be compared to the fully personalised app and control/single program groups via EMI and post/follow-up on parenting and parent/child emotion regulation. Discussion This study introduces a novel digital program combining co-designed parenting content, real-time delivery, tailoring to ensure practical relevance, and algorithm-driven personalisation. By testing standardised and personalised app versions, it will evaluate whether real-time personalised parenting support improves parent/child emotion regulation, engagement, and program acceptability. Findings will inform future approaches to scalable, inclusive, and responsive parenting support in early childhood. Trial registration This trial is registered with ANZCTR, registration number ACTRN12624000937516; ACTRN12624001023549, and includes all items from the WHO Trial Registration Data Set.